2021
DOI: 10.3390/app11041474
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Safety Climate in Construction Sites of Saudi Arabia: A Bootstrapped Multiple Ordinal Logistic Regression Modeling Approach

Abstract: Construction site accidents can be reduced through proactive steps using prediction models developed based on factors that influence the safety climate. In this study, a prediction model of the safety climate observed by construction site personnel in Saudi Arabia was developed, identifying a set of significant safety climate predictors. The model was built with data collected from 401 active construction site personnel using a bootstrapped multiple ordinal logistic regression model. The model revealed five si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(86 reference statements)
1
7
0
Order By: Relevance
“…This corroborates the fact that the construction industry in Saudi Arabia is an indispensable sector of the Kingdom's economy [3], [4]. However, construction projects in Saudi Arabia have been synonymous with accidents despite the industry's significant impact on the nation's economy and the considerable improvements in safety through the years [2]. Remarkably, the rate of accidents in construction projects is second to none compared to any other sector of the economy [5], [6].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…This corroborates the fact that the construction industry in Saudi Arabia is an indispensable sector of the Kingdom's economy [3], [4]. However, construction projects in Saudi Arabia have been synonymous with accidents despite the industry's significant impact on the nation's economy and the considerable improvements in safety through the years [2]. Remarkably, the rate of accidents in construction projects is second to none compared to any other sector of the economy [5], [6].…”
Section: Introductionsupporting
confidence: 65%
“…The construction industry of Saudi Arabian is considered one of the most significant pillars of the nation's economy, and it generates 9.5% of the Kingdom's Gross Domestic Product [1]. About 18% of the country's population is gainfully employed in construction [2]. This corroborates the fact that the construction industry in Saudi Arabia is an indispensable sector of the Kingdom's economy [3], [4].…”
Section: Introductionmentioning
confidence: 71%
“…Cronbach’s alpha was calculated to measure the reliability for sets of latent variables in the used questionnaire, and the overall alpha value for NOSACQ-50 was 0.877, indicating a satisfactory level of reliability because the value exceeded the threshold of > 0.70 [ 11 ]. Table 3 presents descriptive statistics delineating mean and standard deviation values that compare the levels of safety climate between local and multinational employers’ samples by presenting the mean score for each item across the seven dimensions.…”
Section: 0 Results and Data Analysismentioning
confidence: 99%
“…Additionally, it is a vital tool that enables companies to use rubric-based descriptors to evaluate their safety climate maturity in a reliable way [ 9 ], thereby improving safety culture, employee quality of life, and accident prevention [ 10 ]. The importance of SC was emphasized by Makki & Mosly [ 11 ] who argued that it can assist industry owners and contractors by providing details related to attitudes and perceptions that can enhance safety performance. In terms of managerial benefits, the excellence of the safety climate influences three areas: management, site, and enterprise.…”
Section: 0 Introductionmentioning
confidence: 99%
“…The second study revealed that the 13 factors act as determinants of safety climate in construction sites of Saudi Arabia under three key components of safety climate which are safety commitment, safety interaction, and safety support [38]. The third study developed a safety climate prediction model and revealed the set of significant safety climate predictors in construction sites of Saudi Arabia [39]. To further enrich the area of research related to safety climate workers perceptions in the Saudi Arabian construction industry, this study aimed to determine the perceptions and multi-sociodemographic characteristics of construction site personnel regarding the factors that influence the safety climate.…”
Section: Introductionmentioning
confidence: 99%